Reverse juggling processes. Issue 1 (11th December 2018) - Ayyer, Arvind; Linusson, Svante
Abstract : Knutson introduced two families of reverse juggling Markov chains (single and multispecies) motivated by the study of random semi‐infinite matrices over F q . We present natural generalizations of both chains by placing generic weights that still lead to simple combinatorial expressions for the stationary distribution. For permutations, this is a seemingly new multivariate generalization of the inversion polynomial.